IMPLEMENTATION OF PERMA NUMBER 1 OF 2016 CONCERNING MEDIATION IN SETTLEMENT OF INHERITANCE CASES IN SURABAYA RELIGIOUS COURT - Setiawan, Baharudin; Waluyo (Universitas Islam Balitar, 2024)
In this study, the authors used an empirical juridical method, namely research that aims to find out and analyze the implementation of Supreme Court Regulation Number 1 of 2016 concerning Mediation in the settlement of inheritance cases at the Surabaya Religious Court (Case Study: Application for Inheritance at the Surabaya Religious Court), and data sources were obtained from interviews with various parties related to the implementation of mediation at the Surabaya Religious Court, data obtained from the Surabaya Religious Court, legislation, and various literature. The results of this study can be concluded that many inheritance cases in the Surabaya Religious Court have not succeeded in obtaining a peace certificate in the mediation process. Mediation has not been carried out optimally because there are still obstacles both from the Surabaya Religious Court and from external parties. These obstacles include mediators, parties, and attorneys. Based on the results of research conducted by the authors of the various inhibiting factors that arise in the mediation implementation process, there are still efforts that can be made. Efforts made include the parties and attorneys must have good faith in carrying out the mediation.